Social Inclusion Despite Exclusionary Sex Offense Laws: How Registered Citizens Cope With Loneliness: - Ten Bensel, Tusty (Criminal justice policy review, 2019)
The use of social media has become associated with empowerment, social capital, and social inclusion for members of marginalized groups in society. Few groups in today’s social environment are as marginalized, if not more, than sex offenders. This article explores the use of social media among 112 registered sex offenders who are in the community, no longer under correctional control, and self-report no reoffending. Self-reports of desistance were triangulated through interviews with 38 spouses/relatives of registrants and arrest data. Unlike prior studies of sex offenders’ use of social media to facilitate offending, we found the use of social media helps create informal social networks, reduces loneliness, and provides a sense of empowerment among sex offenders and their family members. These are all factors important to promoting public safety and reducing sexual recidivism.